Jual Beli on line (E-Commerce) ditinjau dari Perspektif Hukum Islam - Wakhidah, Wakhidah; Thohari, Chamim (Universitas Muhammadiyah Surabaya, 2018)
AbstrakE-Commerce has a new phenomenon in a trading transation that done by a modern society. Because it’s a new model of transaction, so the istrution law from the moslem scholars has been not founded in any classic fiqh books. Based on the reality, the ulama must to discover its law in Islam pass through ijtihad. The problems which it will be answered pass through this research limited to the following questions: (1) How is implementation of e-commerce? (2) How is implementation of e-commerce perspective of Islamic law? This research is a library research with a normative law research model. It is a research model which purposed to know the relation between arrangements of law and the law norms or the law principels. This research also using comparative approach to seek suitability between the law of e-commerce and fiqh legal maxim. The results of the research there are: (1) The implementation of e-commerce can be explained that consumers choose items to be purchased from the seller's website, then consumers transfer a number of prices to the seller's account and finally the seller sends goods to consumers (2) Based on the fiqh legal maxim, e-commerce is permitted as long as not found some forbidden elements by Islamic law which it incontrary with the Islamic muamalah principels. The conclusion is the implementation of online buying and selling can be explained that consumers choose items to be purchased from the seller's website, then consumers transfer a number of prices to the seller's account and finally the seller sends goods to consumers. As for the review of Islamic law on online buying and selling is permissible as long as there are no elements that are prohibited in Islamic shari'ah which can forbid it and not contradict the principles of muamalah. Keywords: E-Commerce, Islamic Law, Fiqh Legal Maxim, Fiqh Muamalah.